Humanism and the Challenge of Difference (Springer International Publishing, 2018)
This book explores the implication of diversity for humanism. Through the insights of academics and activists, it highlights both the successes and failures related to diversity marking humanism in the US and internationally. It offers a timely depiction of how humanism in general as well as how particular humanist communities have wrestled with the nature of our changing world, and the issues that surface in relationship to markers of difference.